Navigational bronchoscopy: a guide through history, current use, and developing technology - Cicenia, Joseph (J Thorac Dis, 2020)
The peripheral pulmonary nodule offers unique challenges to the clinician, especially in regards to diagnostic approach. Quite often the etiology of the nodule is spurious, though the specter of malignancy drives accurate classification of the nodule. Diagnostic approaches range in degrees of invasiveness, accuracy, and morbidity. Bronchoscopic access to these nodules had been plagued by low reported yields, especially in fluoroscopically invisible nodules. Navigational bronchoscopy, however, allowed more accurate access to peripheral nodules while maintaining a low morbidity, and thus reshaped the historic diagnostic algorithms. Though navigational bronchoscopy was initially associated with electromagnetic navigation, newer approaches to navigation and new technologies provide enthusiasm that yield can improve. In this article we will provide a historical approach to navigational bronchoscopy, from its origins to its current state, and we will discuss developing technology and its potential role in the evolving paradigm of the peripheral nodule biopsy.